The Impact of Virtual-Based Reminiscence Therapy in Older Adults’ Cognitive Function: A Systematic Review - Astuti, Trihaningsih Puji; Indarwati, Retno; Fauziningtyas, Rista (Babali Publisher, 2024)
Introduction: Cognitive decline in older adults is a common challenge that affects their independence and well-being. Virtual-based reminiscence therapy (VBR) is a versatile approach that may enhance memory and cognitive function by revisiting past experiences through digital platforms. This method has the potential to yield better outcomes compared to conventional methods. The objective of this study is to investigate the influence of virtual reality (VR) in reminiscence therapy for improving cognitive function among older adults. Method: A systematic literature review was conducted across five journal databases: Cochrane, ProQuest, PubMed, Scopus, and Web of Science. The screening and selection process adhered to PRISMA 2020 guidelines, and article bias was assessed using the Joanna Briggs Institute (JBI) screening instrument. A narrative analysis was presented to examine the impact of VBR on cognitive function in older adults. Results: This review identified five articles that met the predefined inclusion criteria. The total number of respondents was 250, with an age range from 65.54 to 86.05 years. The cognitive function measurement tools used in the five articles included the Saint Louis University Mental Status (SLUMS) ratings, the Mini-Mental State Examination (MMSE), the Cognitive Assessment Screening Instrument (CASI), and the Addenbrooke's Cognitive Examination III (ACE-III). Conclusion: VR-based reminiscence therapy shows promising potential for enhancing cognitive function among older adults. However, further adaptations are required to accommodate the physical capabilities of older adults in integrating technology into therapeutic practices.